Authenticity and Pedagogical Aspects in an English Textbook for Seventh Grade Students of Junior High School - Lady Cantika Yahya, Shahnaz; Thohir, Lalu; Apgrianto, Kurniawan (Institut Agama Islam Negeri Madura, 2024)
This study deals with the analysis of textbooks for the 7th grade students of junior high school in terms of authenticity and pedagogical. The purpose of this study was to know to what extent the English textbook accomplishes authenticity aspects and pedagogical aspects. This study employed a qualitative descriptive approach. The data were collected through documentation. The data source for this research is the Bupena English textbook for seventh grade students of Junior high school written by Nur Zaida and published by Erlangga in 2018. The textbook analysis for authenticity aspects was identified by using authentic assessment criteria, while for pedagogical aspects, it was based on the criteria made by Cunningsworth (1995). The results of the study show that from the authenticity aspects, the textbook fulfills 7 out of 15 criteria and is categorized as